Hybrid metallic nanoparticles: enhanced bioanalysis and biosensing via carbon nanotubes, graphene, and organic conjugation - Daniele, Michael A.; Pedrero, Maria; Burrs, Stephanie; Chaturvedi, Prachee; Wan Salim, Wan Wardatul Amani; Kuralay, Filiz; Campuzano-Ruiz, Susana; McLamore, Eric; Claussen, Jonathan C.; Cargill, Allison A.; Ding, Shaowei; Claussen, Jonathan C. (Springer, 2015)
Composite materials, incorporating noble metal and metal oxide nanoparticles, have attracted much interest as active substrates for biosensor electronics. These nanoparticles provide a viable microenvironment for biomolecule immobilization by retaining their biological activity with desired orientation and for facilitating transduction of the biorecognition event. Herein, we discuss various methods for fabrication of metal and metal oxide nanoparticle composite materials and their applications in different electrochemical biosensors. The materials are organized by the corresponding component with the nanoparticles, i.e. carbon-based composites, polymers, and DNA. The performance of hybrids is compared and examples of biosensing apparatus are discussed. In all cases, the engineering of morphology, particle size, effective surface area, functionality, adsorption capability, and electron-transfer properties directly impact the resultant biosensing capabilities. Ultimately, these attractive features of metal and metal-oxide hybrid materials are expected to find applications in the next generation of smart biosensors.